Barclays Bank : colluding to manipulate LIBOR - Oji, Chijioke (SAGE knowledge. Cases., 2016)
In late June 2012, the results of a long-term investigation by the United Kingdom's financial watchdog, the Financial Services Authority (FSA), revealed that derivatives traders and bankers at Barclays Bank had been colluding to influence submissions that influenced the London Interbank Offered Rate (LIBOR) and the Euro Interbank Offered Rate (EURIBOR). This book examines the fallout of the scandal.